Clinical Profile of Scabies in Children in the Outpatient Installation of Dr. Moewardi General Hospital Surakarta, the Period of January 2015- December 2019 - Eka Devinta Novi Diana; Alfina Rahma; Frieda; Indah Julianto; Moerbono Mochtar; Suci Widhiati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Scabies is caused by parasite, called Sarcoptes scabiei, infestation into the skin. Scabies isgenerally found in children who live in crowded environments and poor hygiene.Methods: This is a retrospective descriptive study with secondary data collection from medical record datain the Outpatient Installation of RSDM for the period January 2015-December 2019. The subjects wereinfants to children aged 14 years with a diagnosis of scabies. Data variables used included age, gender,family history of scabies, diagnosis, comorbidities, supporting examinations and, therapy in scabies patients.Results: There were 88 pediatric patients with scabies. The most age group that experienced child scabieswas 11-14 years (33%) with the most sex being male (55%). The largest source of scabies transmission wasfrom the family (39%). The most common lesion morphology was papules and excoriations (49%). Thelesion location was found mostly between the fingers (24%). Examination of skin scrapings using NaCl0.9% was positive only in 5 patients (6%) with the most diagnosis was scabies (77%)Conclusion: This study shows that most of pediatric patients with scabies in the 11-14 years range aredominated by males. The most common sources of infection were families with papule morphology andexcoriation, whereas the most lesions were found between the fingers. Skin scrapings are only positive 6%of cases. The most commonly used topical therapies are 5% permethrin and 2% ointment mupirocin whilethe systemic therapies are cetirizine and cefadroxil.